Theory and Practice of Polish Language Teaching: New Methodological Concepts - Gębal, Przemysław E; Janowska, Iwona (Interdisziplinäre Verortungen der Angewandten Linguistik, 2024)
The aim of the volume is to focus on research interests that are rarely presented in the literature on the subject and that arise from the currently perceived needs of the developing didactics of Polish as a foreign language. The research results presented in the contributions provide a new look at the process of acquiring and/or teaching/learning Polish from the following aspects: the peculiarities of Ukrainian speakers learning Polish; problems of acquiring Polish by students from Japan, China, France and Lebanon, methods of developing language skills and activities, and specific phenomena in teaching Polish as a business language. Qualitative, quantitative, and mixed analyses, as well as experimental corpora, allow the results described to be considered important for the developing discipline.